2006
DOI: 10.1123/japa.14.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Yearlong Physical Activity and Health-Related Quality of Life in Older Japanese Adults: The Nakanojo Study

Abstract: We hypothesized that the health-related quality of life (HRQOL) would be poorer in physically inactive older adults. This was tested in a sample of 73 male and 108 female free-living healthy Japanese participants, age 65–85 years. We measured accelerometer step counts and their metabolic equivalents (METs) throughout each 24-hr period for 1 year. At the end of the year, HRQOL was assessed. Physical activity was grouped into quartiles. HRQOL was poorer in the lowest quartiles of participants with respect to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 22 publications
6
54
0
9
Order By: Relevance
“…It should be noted elderly female have more health complaints and lower life quality indicators. Such tendencies have worldwide character and similar results identified in Japan, Brazil, USA and Canada [1,10,11,13]. Women are more often diagnosed with different disorders.…”
Section: Jpes ®supporting
confidence: 64%
See 2 more Smart Citations
“…It should be noted elderly female have more health complaints and lower life quality indicators. Such tendencies have worldwide character and similar results identified in Japan, Brazil, USA and Canada [1,10,11,13]. Women are more often diagnosed with different disorders.…”
Section: Jpes ®supporting
confidence: 64%
“…Life quality according same scale was critical (Emotional Role Functioning, General Health, Bodily Pain). The graph shows the survey results of female from Iran (age -65-69 years) [17], China (age >60 years) [14], Japan (age 65 years) [1], Brazil (age -60-69 years) [11], USA (age -78 years) [13], Canada (age -65-74 years) [10], South Australia (age -65-74 years) [6], Poland (age -45-65 years) [19], Ukraine (own data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be continued 54 The level of PA was stratifi ed into quartiles (1 = least active, 4 = most active) according to the intensity level of PA 3 METs.…”
mentioning
confidence: 99%
“…Several authors have pointed out the importance of QOL of the elderly (Asai et al, 2001;Maeda et al, 2002;Yasunaga and Aoyagi 2006). Arao et al (1998) have demonstrated that QOL is related to living fitness and physical functioning necessary for self-independent life.…”
Section: Introductionmentioning
confidence: 99%